Pemanfaatan Whatsapp Sebagai Media Telekonsultasi Terhadap Ketidaknyamanan Ibu Hamil, Bersalin, dan Nifas di Puskesmas Dolo Kabupaten Sigi - Irnawati, Irnawati; Dyastuti, Nur Eka; Amastasya, Sherin (UKInstitute, 2024)
In 2022, maternal mortality (MMR) in Central Sulawesi reached 67 cases, while infant mortality (IMR) stood at 308 cases. In 2023, these numbers increased to 60 cases for MMR and 417 cases for IMR. WhatsApp, with 83% of users in Indonesia, was utilized in this study as a communication medium to educate pregnant, laboring, and postpartum women through teleconsultation, providing information, motivation, and solutions related to discomforts experienced during these periods. This descriptive study employed a case study approach, examining the discomforts experienced by women from pregnancy through postpartum. The study was conducted at Puskesmas Dolo, Sigi Regency, from March 14 to May 30, 2024, with the subject being Mrs.